PENGARUH BUDAYA ORGANISASI, KOMPETENSI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA CV. PUTRA FIDRA KABUPATEN KARAWANG - Syaefudin Aziz; Riska Apriani; Nuraeni Aziz (EKBIS (Ekonomi & Bisnis), 2020)
The issues raised in this study are: to know, describe and discuss Organizational Culture, Competency And Work Discipline and Employee Performance, and partial and simultaneous influence of Organizational Culture, Competency And Work Discipline On Employee Performance Of CV. Putra Fidra In Karawang Regency. The total number of population is 175 employees, from which taken 125 employees as sample using the Slovin formula. This research use deskriftif and verifikatif methode. The results of analysis data obtained some conclusions as follows: (1) Organization culture is very good, (2) Employee competence is very good, (3) Employee discipline is very good, and (4) Employee performance is very good. There is partial influence Organizational Culture, Competence and Work Discipline on Officers Performance, Organizational Culture have Influence positive and partially significant to Officers Performance, that is equal to 28,3%. Competence have a positive and significant influence partially on Officers Performance, which is equal to 21.9%. Work Discipline have a positive and significant influence partially on Officers Performance, which is equal to 46.9%. There is have positive and significant simultaneous influence between Organizational Culture, Competence and Discipline on Employee Performance. Total simultaneous influence of Organizational Culture, Competence and Work Discipline on Employee Performance, which is equal to 97.1%, while the remaining 2.9% is the influence of other variables (ɛ) not examined.Keywords: Organizational Culture, Competence, Work Discipline and Officers Performance.